PELATIHAN KEWIRAUSAHAAN BAGI MASYARAKAT DI PONDOK PESANTREN DI KOTA BATAM - Dian Lestari Siregar; Evan Rosiska; Jontro simanjuntak (Jurnal Pendekar Nusantara, 2024)
This entrepreneurship training activity is beneficial for the community at the Islamic Boarding School in Batam City. In general, it is going well, this is shown by: The growing spirit, motivation and creativity of the Islamic Boarding School community to explore potential business ideas and a new business business plan can be prepared which will be developed by Islamic boarding school community. Entrepreneurship training events for the community at Islamic boarding schools in Batam City need to be held again involving more participants with more mature timing taking into account the suitability of the activities of the Islamic boarding school community. This is considering the importance of the entrepreneurial spirit that needs to be fostered in society at this time, to reduce the quite large gap between the number of workforce and the number of employment opportunities